2018
DOI: 10.12691/jfnr-6-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Some Phytochemicals and Anti-inflammation Effect of Juice from <i>Tiliacora triandra</i> Leaves

Abstract: Tiliacora triandra (TT), native to Southeast Asia, has been widely used as folk medicine and in cuisines in many areas. Although little scientific evidence supports the health benefits of TT leaves, the juice extracted from TT leaves has become popular for consumers among all socioeconomic classes. Thus, this study aims to evaluate the phytochemical profile and anti-inflammatory properties of juice extracted from TT leaves. The result revealed that, the highest total phenolic contents (199.92 mg GAE/g), total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…We found that T. triandra extract at a concentration of 1250 μg/ml significantly inhibited PRRSV infectivity at a virus titer of 3.5 TCID 50 (log10). While T. triandra extract has been used as anti-inflammatory [22], anticancer [23], and antimicrobial agents against Mycobacterium tuberculosis [24], its antiviral activity, particularly against PRRSV, has not been investigated previously. Therefore, this is the first report to indicate that T. triandra extract could significantly prevent the entry of PRRSV into MARC-145 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that T. triandra extract at a concentration of 1250 μg/ml significantly inhibited PRRSV infectivity at a virus titer of 3.5 TCID 50 (log10). While T. triandra extract has been used as anti-inflammatory [22], anticancer [23], and antimicrobial agents against Mycobacterium tuberculosis [24], its antiviral activity, particularly against PRRSV, has not been investigated previously. Therefore, this is the first report to indicate that T. triandra extract could significantly prevent the entry of PRRSV into MARC-145 cells.…”
Section: Discussionmentioning
confidence: 99%
“…All studied plant extracts could inhibit PRRSV replication when applied at high Regarding phytochemical content, C. sappan extract had the highest total phenolic content (220.52 ± 4.47 mM GAE/g sample). The total phenolic content of a plant is considered an indicator of its antioxidant capacity because the redox properties of phenolic compounds allow them to act as reducing agents, hydrogen donors, and radical scavengers [22]. Previously, Lee et al [26] reported that ethanolic C. sappan extract had a total phenolic content of 723.67 μg GAE/mg.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates the pharmacological effect of Tiliacora triandra (Colebr) Diels leaf aqueous extracted (TTE) under diabetic conditions by exhibiting antidiabetic, antioxidant, and hepatoprotective effects mainly through inhibition of the gluconeogenesis pathway. Several studies have shown that the water and/or methanol and ethanol extracts of Tiliacora triandra (Colebr) Diels leaves have beneficial effects, such as antioxidant, neuroprotective, hypoglycemic, and inhibition of cholesterol absorption activities due to a variety of active components [ 13 , 14 , 15 , 16 , 17 , 18 ]. To assess the potential and safe use of TTE as a nutraceutical product to prevent hepatic glucose overproduction in diabetes, this study extracted TTE in water and identified phenolic compounds from TT leaves.…”
Section: Discussionmentioning
confidence: 99%
“…This study also clearly demonstrates that treatment with TTE and its major active components suppress hepatic glucose production induced by an amino acid mixture, reduced oxidative stress by scavenging free radicals, and induced antioxidative gene synthesis in hepatocytes, in which hyperglycemia induced-oxidative stress triggers the development of insulin resistance and a consequent of hepatic glucose overproduction [ 19 ]. Within this context, the higher antioxidant activity of phenolic compounds extracted from water (TTE) is also demonstrated when compared with ethanol and acetone extracts of Tiliacora triandra [ 16 ]. Similarly, TTE exerts antioxidant and neuroprotective effects in neurodegenerative rats induced by ethanol [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation